STANDARDS OF PRODUCT MARKETING TRACEABILITY FISHERY - Приліпко, Тетяна; Федорів, Віктор (Modern engineering and innovative technologies, 2023)
Currently, for European countries, the issue of organization, implementation and control of integrated multi-year monitoring plans developed in accordance with the requirements of Regulation of the Parliament and the Council of the EU No. 882/2004 is extr